1992
DOI: 10.23986/afsci.72448
|View full text |Cite
|
Sign up to set email alerts
|

Milk production and concentrations of blood metabolites as influenced by the level of wet distiller’s solubles in dairy cows receiving grass silage-based diet

Abstract: Miettinen, H. 1992. Milk production and concentrations ofblood metabolites as influenced by the level of wet distiller's solubles in dairy cows receiving grass silage-based diet. Agric. Sci

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Milk production increased (P < 0.01) when fed CCDS, but there was no advantage of feeding the higher instead of lower amounts of CCDS (Table 4). This finding agreed with Huhtanen and Miettinen (1992), who observed increased production when cows were fed 5.9% of their feed DM as wet distillers solubles, but no addi- tional production when fed up to 17.5% of the ration DM as solubles. Increased production because of addedfat diets have been observed in several studies (Palmquist and Jenkins, 1980;Schingoethe and Casper, 1991).…”
Section: Lactational Responsessupporting
confidence: 92%
See 1 more Smart Citation
“…Milk production increased (P < 0.01) when fed CCDS, but there was no advantage of feeding the higher instead of lower amounts of CCDS (Table 4). This finding agreed with Huhtanen and Miettinen (1992), who observed increased production when cows were fed 5.9% of their feed DM as wet distillers solubles, but no addi- tional production when fed up to 17.5% of the ration DM as solubles. Increased production because of addedfat diets have been observed in several studies (Palmquist and Jenkins, 1980;Schingoethe and Casper, 1991).…”
Section: Lactational Responsessupporting
confidence: 92%
“…Milk production was increased slightly when cows were fed condensed distillers solubles processed from a mash blend of 60 to 70% corn, 16 to 18% rye, and 12 to 14% barley (Udedibie and Chase, 1988) that contained more protein and less fat than the CCDS used in our study. A study in Finland (Huhtanen and Miettinen, 1992) used wet distillers solubles that likewise contained more protein but less fat than solubles routinely available in the United States and also observed slightly increased milk production. Distillers solubles are usually blended with distillers grains to make distillers grains with solubles, which is marketed as wet or dried distillers grains with solubles.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the inclusion of WDS in grain-based concentrate on milk production is in line with results from our previous experiment (Huhtanen and Miettinen, 1992). The positive response to WDS may be related to increased ruminal propionate production from WDS lactic acid rather than to an increased supply of amino acids.…”
Section: The Effect Of Wet Distillers' Solublessupporting
confidence: 89%
“…Rapeseed meal (RSM), the most important domestic protein supplement in Finland, has produced similar responses to those observed with soya-bean meal in the studies cited above (Tuori, 1992). starch-ethanol production increased milk and protein yield when used as a protein supplement for a grass silage-barley diet (Huhtanen and Miettinen, 1992). starch-ethanol production increased milk and protein yield when used as a protein supplement for a grass silage-barley diet (Huhtanen and Miettinen, 1992).…”
Section: Introductionmentioning
confidence: 77%
“…If a substantial amount of silage lactate is converted to propionate in the rumen, it can make a significant contribution to the glucose supply via gluconeogenesis in the liver. Decreased milk fat content and fat yield in cows fed silage of high LA content rather than silage of restrictive fermentation (Honig & Rohr 1973;Heikkila et al 1989;Chamberlain et al 1990) or increased lactose content and yield when barley was gradually replaced with barley distillers' solubles (150-200 g LA/kg DM) (Huhtanen & Miettinen 1992), probably reflect changes in the rumen fermentation pattern due to LA intake and subsequently in the supply of milk precursors. However, Gill et al (1986) found that LA was metabolized in sheep mainly to acetate and the contribution of lactate to the glucose supply through propionate was not more than 01 of total lactate.…”
Section: Discussionmentioning
confidence: 99%